PRINCIPAL LEADERSHIP IN IMPROVING EDUCATIONAL PERFORMANCE IN INTEGRATED ISLAMIC HIGH SCHOOL OF RIAU ISLANDS PROVINCE - Faisal Hakim Nasution; Kasful Anwar; Kemas Imron Rosadi; Asrulla Asrulla (PT. Jurnal Center Indonesia Publisher, 2025)
The challenges of modern education demand not only academic achievement but also the cultivation of students’ noble character. In this context, the role of principals in Integrated Islamic Senior High Schools (SMA IT) becomes highly strategic. This study aims to analyze and describe the role and influence of principals’ Islamic integrative leadership on improving the performance of educational staff within SMA IT. A qualitative approach with a phenomenological method was employed. Data were obtained through in-depth interviews with principals and educational staff as well as participant observation. Analysis was conducted interactively through data reduction, presentation, and conclusion drawing. The findings show that Islamic integrative leadership which combines modern leadership models such as transformational, instructional, democratic, servant, and distributive leadership with Islamic values such as exemplary conduct (uswah hasanah), consultation (syura), trustworthiness (amanah), justice, and a clear vision significantly enhances the performance of educational staff. The integration of these values creates a work culture imbued with a spirit of worship, collaboration, and quality orientation. Educational staff become more motivated, loyal, and productive as they view their work as part of worship. This study concludes that Islamic integrative leadership is not merely a leadership style but an effective organizational culture foundation at SMA IT. Its implementation has been proven to empower educational staff, improve their performance, and support the achievement of sustainable Islamic educational goals. This leadership model is recommended for broader development in Islamic educational institutions.